1995
DOI: 10.1002/ijc.2910600215
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic effect of the 15‐kDa gross cystic disease fluid protein (GCDFP‐15) on breast‐cancer cell lines and on immortal mammary cells

Abstract: The biological significance of a major protein component in the fluid of gross cystic breast disease and a recognized marker component protein in breast gross cystic disease fluid and is Dresent at a concentration of aDDroximatelv 30 mg/ml. I I of apocrine-metaplasia, i.e. the I5-kDa glycoprotein (GCDFP-15). is presently unknown. We have added GCDFP-I5 to cell culture medium and tested its effect on proliferation of human breast-cancer cell lines (MCF7, BT474, MDA-MB23 I and ~4 7~) and a "normal" human immorta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 12 publications
0
24
1
Order By: Relevance
“…Cassoni et al [12] has demonstrated the effect of PIP in the proliferation of 4 human breastcancer cell lines (MCF7, BT474, MDA-MB231 and T47D) and in a "normal" human immortal breast-cell line (MCF10A). Interestingly, these breast-cell lines showed a mitogenic response to PIP (10 mg/mL) with an enhanced cell growth.…”
Section: Tumor Progression and Biomarkermentioning
confidence: 99%
See 1 more Smart Citation
“…Cassoni et al [12] has demonstrated the effect of PIP in the proliferation of 4 human breastcancer cell lines (MCF7, BT474, MDA-MB231 and T47D) and in a "normal" human immortal breast-cell line (MCF10A). Interestingly, these breast-cell lines showed a mitogenic response to PIP (10 mg/mL) with an enhanced cell growth.…”
Section: Tumor Progression and Biomarkermentioning
confidence: 99%
“…PIP also has high affinity for CD4-TCR (cluster of differentiation -T cell receptor), which modulates the immune response during the viral infection by interfering with the functions mediated by CD4 [6,10]. Recently, many studies have documented for PIP expression in breast and prostate carcinomas and its mitogenic activity on breast cancer cell lines [11], which correlates its active role in tumor proliferation [12]. Finally, it was designated as a sensitive and specific marker for monitoring and defining apocrine differentiation in breast cancer [13].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular pathophysiologic and clinical interest is the presence both of some neuropeptides (e.g., gastrinreleasing peptide and calcitonin gene-related peptide) [99,120,225] and GCDFP-15 [226]; their immunolocalization in cyst-lining apocrine epithelium demonstrates their local synthesis and the potential role in BC risk development, mainly due to their mitogenic properties regulating apocrine metaplastic transformation [120,226]. Moreover, the relationship between BCF and plasma levels of GCDFP-15 may be useful in identifying groups of women with active GCBD who are at increased risk of developing BC [140].…”
Section: Miscellaneous Biocompoundsmentioning
confidence: 99%
“…The function of PIP is not known, but it is suspected to play a role in host defense against pathogens [1][2][3][4][5][6] because it is expressed in tissues strategically located at several T-cell apoptosis induced by sequential CD4/T-cell receptor triggering, which in part modulates the immune response during viral infection by interfering with the functions mediated by the CD4 molecule [5,6,14]. Furthermore, PIP has been reported to exhibit a mitogenic effect for both normal and malignant breast epithelial cells [15], strongly suggesting that it might play a critical role in differentiation, proliferation, and function of immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…45: 1082-1091 Immunity to infection 1083 T-cell apoptosis induced by sequential CD4/T-cell receptor triggering, which in part modulates the immune response during viral infection by interfering with the functions mediated by the CD4 molecule [5,6,14]. Furthermore, PIP has been reported to exhibit a mitogenic effect for both normal and malignant breast epithelial cells [15], strongly suggesting that it might play a critical role in differentiation, proliferation, and function of immune cells.Our previous studies show that PIP KO mice have enlarged submandibular lymph nodes and thymic medulla [16]. However, to date, no studies have addressed the contributions of PIP in T-cell responses to either model Ags or infectious agents.…”
mentioning
confidence: 99%